1, 6, 7-Trisubstituted perylene bisimides with tunable optical properties for colorimetric and "turn-on" fluorescence detection of HCl. (June 2022) - Padghan, Sachin D.; Chung, Min-Chieh; Zhang, Qi-Sheng; Lin, Wei-Chun; Chen, Kew-Yu
Abstract: To elucidate the effect of different substituents on the optical and redox properties of perylene bisimide (PBI), a novel series of 1, 6, 7-trisubstituted PBIs (1 –6 ) with a highly twisted perylene core was synthesized and characterized. By substituting the hydrogen atoms at the bay-positions with various substituents (dihexylamino, piperidinyl, morpholinyl, hexoxy, and bromo), the absorption and fluorescence wavelengths of 1 –6 in cyclohexane were extensively tuned within the ranges of 551–646 and 586–720 nm, respectively, simply by harnessing the electron-donating strength of the substituents. Varying the substituents generated a new family of long-wavelength absorbing and fluorescent dyes. Moreover, PBI 2 exhibited colorimetric and "turn-on" fluorescence responses in extremely acidic medium (pH 1.0 to −0.6). Low-cost test strips containing 2 were easily prepared and could be used to detect HCl. Graphical abstract: Image 1 Highlights: A series of 1, 6, 7-trisubstituted perylene bisimides (1 –6 ) was synthesized. The emission wavelengths of 1 –6 can be widely tuned from 586 to 720 nm. Compound 2 exhibits colorimetric and fluorometric responses to HCl.